Optimization of economic/environmental operation management for microgrids by using hybrid fireworks algorithm. (21st September 2017) - Wang, Zhenyu; Zhu, Qibing; Huang, Min; Yang, Bao
Summary: The wide use of renewable energy sources stimulates the implementation of microgrid (MG) systems. MG is an independent power system that consists of various distributed generations (DGs), storage devices, and loads. The optimization problems of MG have gained wide spread interest considering the economic and environmental operation management of the system. To address the multi‐variable non‐linear programming problem with multiple hybrid constraints, this paper proposes a novel hybrid multi‐objective fireworks algorithm with gravitational search operator (MFAGSO). In the algorithm, the operator, as a new search mechanism, directs the sparks in the clustered region to exchange positional information with Pareto‐optimal solutions at each iteration process for obtaining accurate results. The operation management of typical grid‐connected MG, which comprises various DGs and storage battery, was optimized within 24 hours to evaluate the performance of the proposed algorithm. Considering operation cost and pollutant emission individually or simultaneously, 3 scenarios were involved in operation management for power market planning and practical considerations. The simulation results of the proposed algorithm were compared with those from other methods employed in previous literature and original fireworks algorithm. The results demonstrated the superior performance of the proposed method to solve operation management for optimizing problems of MG.